Extending the Concept of Advance Care Planning to the Perinatal Period - Garten, Lars; von der Hude, Kerstin; Strahleck, Thomas; Krones, Tanja (Klinische Pädiatrie, 2020)
Easier access to prenatal diagnostic procedures led to its widespread use as a screening measure. Hence, today it is more common for life-limiting illnesses to be diagnosed during fetal life. The concept of Advance Care Planning (ACP) provides a framework for caregivers, families and their multidisciplinary teams to anticipate and plan ahead for potential future medical decisions so that the affected children are reliably treated according to their parents’ individual values and wishes. In the perinatal context, ACP also has the potential to tackle the needs of unborn or newborn children with life-limiting illnesses and their families better, avoid unnecessary and burdensome measures and focus upon goals that are valuable and meaningful to both child and family.
Keywords: neonate; pregnancy; life-limiting disease; palliative care; birth plan; prenatal counselling